Performance of seismically substandard bridge reinforced concrete columns subjected to subduction and crustal earthquakes. (15th March 2020) - Lopez, Alvaro; Dusicka, Peter; Bazaez, Ramiro
Highlights: Large-scale experiments performed on a shake table are presented. The specimens were subjected to subduction and crustal ground motions with distinctive durations. More damage was recorded in the specimens subjected to subduction ground motions. Ground motion duration affects displacement capacity and failure mode of bridge columns. Abstract: The recent occurrence of highly damaging, long-duration subduction earthquakes in Chile (Maule, 2010) and Japan (Tohoku, 2011), has highlighted the importance of better understanding the effects of ground motion duration on structural performance. With that aim, an experimental program was conducted to study the effects of ground motion duration exhibited by subduction earthquakes on the performance of reinforced concrete bridge columns. The results of shake table experiments on large-scale circular reinforced concrete columns that were subjected to subduction and crustal ground motions are presented. The specimens were chosen to reflect common reinforced concrete bridge columns, which were built prior to mid-1970 in the Pacific Northwest of the United States and thereby designed and constructed using seismic procedures currently considered substandard. The results showed that ground motion duration can affect the displacement capacity and influence the failure mode of these types of bridge columns. Despite achieving similar levels of deformations, more damage was recorded in the specimens subjected to subduction ground motions as compared to crustal. This increased damage was confirmed with visual observations as well as calculated cumulative displacement ductility for each specimen. Measured material strains are also presented and compared to strain limits used in other literature for two-level performance criteria. The results have shown that subduction ground motions can impose higher material strains and result in reinforcement bar buckling that is not necessarily achieved under similar displacement demands from crustal ground motions.